Risk Factors and Predictors of Significant Chondral Surface Change From Primary to Revision Anterior Cruciate Ligament Reconstruction: A MOON and MARS Cohort Study. Issue 3 (March 2018) - ; Magnussen, Robert A.; Borchers, James R.; Pedroza, Angela D.; Huston, Laura J.; Haas, Amanda K.; Spindler, Kurt P.; Wright, Rick W.; Kaeding, Christopher C.; Allen, Christina R.; Anderson, Allen F.; Cooper, Daniel E.; et al.
Background: Articular cartilage health is an important issue following anterior cruciate ligament (ACL) injury and primary ACL reconstruction. Factors present at the time of primary ACL reconstruction may influence the subsequent progression of articular cartilage damage. Hypothesis: Larger meniscus resection at primary ACL reconstruction, increased patient age, and increased body mass index (BMI) are associated with increased odds of worsened articular cartilage damage at the time of revision ACL reconstruction. Study Design: Case-control study; Level of evidence, 3. Methods: Subjects who had primary and revision data in the databases of the Multicenter Orthopaedics Outcomes Network (MOON) and Multicenter ACL Revision Study (MARS) were included. Reviewed data included chondral surface status at the time of primary and revision surgery, meniscus status at the time of primary reconstruction, primary reconstruction graft type, time from primary to revision ACL surgery, as well as demographics and Marx activity score at the time of revision. Significant progression of articular cartilage damage was defined in each compartment according to progression on the modified Outerbridge scale (increase ≥1 grade) or >25% enlargement in any area of damage. Logistic regression identified predictors of significant chondral surface change in each compartment from primary to revision surgery. Results: A total of 134 patients were included, with a median age of 19.5 years at revision surgery. Progression of articular cartilage damage was noted in 34 patients (25.4%) in the lateral compartment, 32 (23.9%) in the medial compartment, and 31 (23.1%) in the patellofemoral compartment. For the lateral compartment, patients who had >33% of the lateral meniscus excised at primary reconstruction had 16.9-times greater odds of progression of articular cartilage injury than those with an intact lateral meniscus ( P < .001). For the medial compartment, patients who had <33% of the medial meniscus excised at the time of the primary reconstruction had 4.8-times greater odds of progression of articular cartilage injury than those with an intact medial meniscus ( P = .02). Odds of significant chondral surface change increased by 5% in the lateral compartment and 6% in the medial compartment for each increased year of age ( P ≤ .02). For the patellofemoral compartment, the use of allograft in primary reconstruction was associated with a 15-fold increased odds of progression of articular cartilage damage relative to a patellar tendon autograft ( P < .001). Each 1-unit increase in BMI at the time of revision surgery was associated with a 10% increase in the odds of progression of articular cartilage damage ( P = .046) in the patellofemoral compartment. Conclusion: Excision of the medial and lateral meniscus at primary ACL reconstruction increases the odds of articular cartilage damage in the corresponding compartment at the time of revision ACL reconstruction. Increased age is a risk factor for deterioration of articular cartilage in both tibiofemoral compartments, while increased BMI and the use of allograft for primary ACL reconstruction are associated with an increased risk of progression in the patellofemoral compartment.